Increasing the Public Speaking Skills of Al Adzkia Islamic Boarding School Students, Riau Islands through Master of Ceremony Training in English - Layla, Muslena; Megawati, Megawati (Jurnal Ilmiah Mandala Education (JIME), 2023)
Abilitypublic speaking It's not easy and it's owned by everyone. So it must be educated so that it has good soft skills. One application abilitypublic speaking is by beingmaster of ceremony (mc). Ability enhancementpublic speaking through English-speaking MC training is able to be the right answer to the problems that occur. In this study using a Qualitative Descriptive Research Method and using Data Collection Techniques such as Documentation, Observation and Interview with the research location at the Al-Adzkia Islamic Boarding School in the Riau Archipelago, by involving all students in the school. As many as 13 students at the junior high school level, 14 students at the high school level along with English teachers and staff from the Islamic boarding school witnessed and participated in the training and mentoring carried out by the English language study program at STAIN Sultan Abdurrahkan Riau Islands. This research was able to run smoothly and received very good feedback from the participants. This can be proven by the results of the questionnaire which stated that they more than agreed that the material provided was sufficient to become an MC with the answers 22.6% answered strongly agreed, 38% answered agreed, 25.8% answered neutral, 12.9% answered disagree. Then the answers from the results of other questionnaires explained that the speaker had presented the material well, so that it was easy to understand and then it could be implemented properly by the participants as evidenced by the number of answers 48.4% agreed, 32.3% answered strongly agreed, and only 19 .4% answered neutral.